Estudo integrado das etapas de pré-tratamento e hidrólise enzimática da palha de cana-de-açúcar - Rocha, Martha Suzana Rodrigues dos Santos (Universidade Federal de São Carlos, 2017)
The use of lignocellulosic biomass for ethanol production, such as, the sugarcane straw, suggests that additional steps should be included aiming the sugars release, that will be converted to ethanol via fermentative route. In this way, it is essential to conduct a pretreatment step, to disrupt partially the recalcitrant structure, increasing cellulose accessibility to hydrolysis by cellulases. This work aims the study of pretreatment and enzymatic hydrolysis strategies of sugarcane straw. The goal is evaluate the best configuration to bioethanol production, taking into account key factors correlated to these two steps. Firstly, the hydrothermal pretreatment (HPT) was conducted in a straw/water ratio of 1:5 to 1:20 (w/v), at 195°C, 10 min and 200 rpm. HPT was followed by alkaline pretreatment (APT, H2O2 1% v/v, pH 11.5). An experimental design (variables: ratio of wdry straw /vwater during the HPT and temperature during the APT) was performed to choice and optimization of the operational conditions. On enzymatic hydrolysis step, 20 FPU/gcellulose and 15% (w/v) of solid loading were applied. The experimental design responses were: cellulose content and cellulose-to-glucose conversion. It was observed that the enzymatic hydrolysis was not improved after the alkaline pretreatment. Thus, taking into account the high efficience of the hydrothermal pretreatment identified in this study, operational costs concerning the alkaline step can be eliminated. In a study concerning HPT mathematical modeling, the assays were conducted applying 10% (w/v) of solid loading and by vary the temperature (180 a 210°C) and time of reaction (0 to 40 min), aiming the identification, from a proposed kinetic model, the optimal temperature and time regarding to sugars degradation and inhibitors formation. At 195 °C/15 min, the pretreatment reached 85% of hemicellulose removal. This condition promoted a little degradation of cellulosic fraction, only 21%. The models proposed in this work can be utilized for engineering studies, including technical and economic feasibility analysis of 2G ethanol production. In addition to the studies developed in this thesis, enzymatic hydrolysis assays were performed in stirred tank reactors, with a reaction volume of 50-mL, applying solids loading of 10, 20, and 30% (w/v), in batch and fed-batch modes. Experiments were conducted in 3-L working volume, under different feeding strategies of substrate/enzyme (fed-batch), reaching 30% (w/v) of solids loading. The assays showed that as the solids loading increases, a decrease in the cellulose-to-glucose conversion is observed. The experiments conducted in fed-batch mode showed high performance when compared with those performed in batch mode. An increase of 3.4 (10% w/v); 9.2 (20% w/v) and 19.8 % (30% w/v) in the cellulose-to-glucose conversion was obtained, taking into account the assays performed in fed-batch mode. Concerning the assays conducted in 3-L working volume, the results showed that the best condition was the one where the feeding profile was smoother (lower solid concentration added in each feed time, but more substrate additions). Both the power consumption per unit volume and the rheology presented lower values to the condition where the feeding profile was smoother. This behavior indicates that this operational mode is more suitable from process point of view, reaching results industrially feasible in terms of glucose content and the energy consumption.
Integrated study of pretreatment and enzymatic hydrolysis steps of sugarcane straw
Keywords: Palha de cana-de-açúcar; Pré-tratamento hidrotérmico; Estudo cinético; Consumo de potência; Batelada alimentada; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA